Structured COBOL - Philippakis, Andreas S. (Manila, Philippines : Merriam & Webster Bookstore, 1986)
This book has been designed to facilitate the learning of COBOL. It includes thorough coverage of concepts, as well as examples of applications, at both elementary and intermediate levels of complexity. Review sections are included in the text as opportunities for the reader to enhance effective learning through self-testing. Students in business administration and computer science will find this book to be a suitable guide to the language.
Section 1. Basic concepts of business data processing -- Section 2. Computers and computer hardware -- Section 3. Computer software and programming -- Section 4. Advanced software systems -- Section 5. System design and development -- Section 6. Basic programming.
Includes index.
Keywords: BASIC (COMPUTER PROGRAM LANGUAGE)